2016
DOI: 10.1007/s10531-016-1269-5
|View full text |Cite
|
Sign up to set email alerts
|

17 years of grassland management leads to parallel local and regional biodiversity shifts among a wide range of taxonomic groups

Abstract: Conservation management is expected to increase local biodiversity, but uniform management may lead to biotic homogenization and diversity losses at the regional scale. We evaluated the effects of renewed grazing and cutting management carried out across a whole region, on the diversity of plants and seven arthropod groups. Changes in occurrence over 17 years of intensive calcareous grassland management were analysed at the species level, which gave insight into the exact species contributing to regional homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 65 publications
0
9
1
1
Order By: Relevance
“…Remarkably, we were unable to detect trends in CPUEC or CPUES over the 43 years covered by the data set, suggesting that carabid populations have not declined in abundance or diversity in arable fields on broader geographical scale over this period. This result is in contrast to the monitoring programmes on local (Poszgai, Baird, Littlewood, Pakeman & Young 2016;van Noordwijk et al 2017) or national scales (Brooks et al 2012;Ewald et al 2015), which have found carabid populations to have declined over time, as well as with general perception that insect populations decline in terrestrial ecosystems (Eggleton 2020;van Klink et al 2020). Since the present data set originates from many local independent studies performed in different years, it is less sensitive to site-specific inter-annual fluctuations (Kotze et al 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…Remarkably, we were unable to detect trends in CPUEC or CPUES over the 43 years covered by the data set, suggesting that carabid populations have not declined in abundance or diversity in arable fields on broader geographical scale over this period. This result is in contrast to the monitoring programmes on local (Poszgai, Baird, Littlewood, Pakeman & Young 2016;van Noordwijk et al 2017) or national scales (Brooks et al 2012;Ewald et al 2015), which have found carabid populations to have declined over time, as well as with general perception that insect populations decline in terrestrial ecosystems (Eggleton 2020;van Klink et al 2020). Since the present data set originates from many local independent studies performed in different years, it is less sensitive to site-specific inter-annual fluctuations (Kotze et al 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…Analyses of faunal responses to ecological restoration are accumulating rapidly and increasingly include responses to created habitat (Andrews et al ; Goldspiel et al ), often utilizing a chronosequence approach (van Noordwijck et al ; Fernandes et al ), including the Nachusa Grasslands chronosequence (Wodika & Baer ; Griffin et al ; Barber et al 2017 a ). We present several lines of evidence to suggest that snakes have responded positively to created habitat at Nachusa Grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…Animal responses to grassland restoration are often characterized using community metrics such as species richness, species diversity, and functional diversity. These metrics show varying patterns in relation to time since restoration (Wodika & Baer ; van Noordwijk et al ; Barber et al 2017 a ), sometimes paralleling plant community metrics (Sluis ; Hansen & Gibson ). Because snake species are few, we characterize snake responses to grassland restoration using probability of occupancy, a species‐level metric of occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The few long‐term trapping studies of carabids have focused mostly on heathland and grassland species (e.g. Hallmann et al ., ; van Noordwijk et al ., ). On local and country level, long‐term studies on carabids demonstrate in general a declining trend of species numbers and biomass (Hallmann et al ., ; Kotze et al ., ).…”
Section: Introductionmentioning
confidence: 97%